Representações das relações entre classes sociais em duas novelas brasileiras: Cheias de Charme e Avenida Brasil - Piqueira, Mauricio Tintori (2017)
This doctoral thesis aims to analyze the ‘soap operas’ Cheias de Charme and Avenida Brasil, transmitted throughout Brazil in the year of 2012. It takes both of them from the point of view of the representations on the Brazilian sociability, in a context marked by increase of the income of part of working class – which supposedly elevated their status to the “new middle class”. This was due through social policies of assistance to the poor, to creation of formal job vacancies in industry, commerce and services, and to the recognition of labor rights guaranteed by legislation for precarious jobs during the Luiz Inácio Lula da Silva (2003-2010) and Dilma Rousseff (2011-2016)’s governments. From the audiovisual narratives of the two “telenovelas”, we conclude that the main Brazilian cultural industry company (TV Globo), transformed into a show the contradictions of a reality in which the “social inclusion by consumption” were insufficient to guarantee the basic rights of citizenship for groups historically relegated to poverty. This has boosted the reaction of the elites as to the alleged “lose of their privileges” that distinguish them from the exploited groups